Shear transfer capacity of reinforced concrete exposed to fire. (April 2018) - Ahmad, Subhan; Bhargava, Pradeep; Chourasia, Ajay
Abstract: Shear transfer capacity of reinforced concrete elements is a function of concrete compressive strength and reinforcement yield strength. Exposure of concrete and steel to elevated temperature reduces their mechanical properties resulting in reduced shear transfer capacity of RC elements. The objective of present study is to find the effect of elevated temperature on shear transfer capacity of reinforced concrete. For this purpose pushoff specimens were casted using normal strength concrete. After curing, specimens were heated to 250°C and 500°C in an electric furnace. Cooled specimens were tested for shear transfer capacity in a universal testing machine. It was found that shear transfer capacity and stiffness (slope of load-slip curve) were reduced when the specimens were heated to 250°C and 500°C. Load level for the initiation of crack slip was found to be decreased as the temperature was increased. A simple analytical approach is also proposed to predict the shear transfer capacity of reinforced concrete after elevated temperature.